2021
DOI: 10.3390/polym13183077
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Trace-Level Ammonia Gas Sensing Based on Flexible PAni-CoFe2O4 Nanocomposite Film at Room Temperature

Abstract: In this study, we developed a new chemi-resistive, flexible and selective ammonia (NH3) gas sensor. The sensor was prepared by depositing thin film of polyaniline-cobalt ferrite (PAni-CoFe2O4) nanocomposite on flexible polyethylene terephthalate (PET) through an in situ chemical oxidative polymerization method. The prepared PAni-CoFe2O4 nanocomposite and flexible PET-PAni-CoFe2O4 sensor were evaluated for their thermal stability, surface morphology and materials composition. The response to NH3 gas of the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Nanocomposite magnetic materials based on polyconjugated polymers are new generation materials with physical and chemical properties required for modern technologies [ 1 , 2 , 3 , 4 , 5 ]. These magnetic nanocomposites can find potential application as hybrid electrocatalysts [ 6 , 7 ], as cathode materials for rechargeable batteries and fuel cells [ 8 , 9 , 10 ], as active materials in solar cells [ 11 , 12 , 13 ] and supercapacitors [ 14 , 15 , 16 , 17 , 18 ], for the remediation of water resources [ 19 , 20 , 21 , 22 , 23 , 24 ], ion-exchange materials [ 25 , 26 , 27 ], ion-specific electrodes [ 28 , 29 , 30 , 31 ], to produce sensors [ 32 , 33 , 34 , 35 , 36 ], as anticorrosive coatings [ 37 , 38 , 39 , 40 ], as electromagnetic radiation absorbing materials [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocomposite magnetic materials based on polyconjugated polymers are new generation materials with physical and chemical properties required for modern technologies [ 1 , 2 , 3 , 4 , 5 ]. These magnetic nanocomposites can find potential application as hybrid electrocatalysts [ 6 , 7 ], as cathode materials for rechargeable batteries and fuel cells [ 8 , 9 , 10 ], as active materials in solar cells [ 11 , 12 , 13 ] and supercapacitors [ 14 , 15 , 16 , 17 , 18 ], for the remediation of water resources [ 19 , 20 , 21 , 22 , 23 , 24 ], ion-exchange materials [ 25 , 26 , 27 ], ion-specific electrodes [ 28 , 29 , 30 , 31 ], to produce sensors [ 32 , 33 , 34 , 35 , 36 ], as anticorrosive coatings [ 37 , 38 , 39 , 40 ], as electromagnetic radiation absorbing materials [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , …”
Section: Introductionmentioning
confidence: 99%
“…Progress in the creation of novel multifunctional magnetic nanomaterials is due to the development of new synthesis methods for nanostructures. The most common method of obtaining hybrid magnetic nanocomposites is oxidative polymerization of monomers (aniline [ 8 , 9 , 25 , 29 , 32 , 51 , 55 , 56 ], pyrrole [ 28 , 40 , 44 , 57 ] and thiophene [ 23 ]) in a reaction medium containing prefabricated magnetic nanoparticles (Fe 3 O 4 [ 25 , 28 , 29 , 42 , 55 , 58 ], γ -Fe 2 O 3 [ 32 , 43 ], α -Fe 2 O 3 [ 37 ], Co 3 O 4 [ 8 , 9 , 38 , 50 ] and CoFe 2 O 4 [ 33 , 59 ]). One of the ways to prevent the metal nanoparticles aggregation is their stabilization in a polymer matrix during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Among ICPs, polyaniline (PANI) is extensively employed for sensing applications due to its easy synthesis, exceptional doping/de-doping chemical reaction, high conductivity, outstanding environmental stability, and excellent responsivity to NH 3 [10]. The incorporation of n-type metal oxide semiconductors, such as In 2 O 3 , SnO 2 , CeO 2 , CoFe 2 O 4 , or carbon-based materials into ICPs can improve the sensing performances of fabricated nanocomposites [11][12][13][14][15][16][17][18]. Xue et al reported that a PANI/carbon nanotube (CNT) composite showed enhanced sensing performance and stability at room temperature as compared to that of pure PANI [12].…”
Section: Introductionmentioning
confidence: 99%
“…Saleh et al prepared an ammonia gas sensor by depositing a PANI/CeFe 2 O 4 nanocomposite on flexible PET film. Their results showed excellent ammonia gas-sensing performance in the range of 1-50 ppm at room temperature [17]. Indium trioxide (In 2 O 3 ), with high optical transparency and electrical conductivity, is widely used in liquid crystal displays and sensors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, conducting polymers based robust and ultra-sensitive sensors of biologically active compounds have been developed for their potential applications in biomedical diagnostics, the food and beverage industry, and environmental analysis [12,13]. Similarly, gas and volatile organic compound (VOC) sensors based on semiconducting metal oxides are also important for various safety and environmental control issues [14][15][16][17]. Likewise, the πconjugated organic semiconductors (consisting of oligomeric/polymeric chain molecules) are a diverse set of materials that have been recently studied to develop cost-effective humidity sensors with superior sensitivity, reproducibility in response, and widespread bandwidth.…”
Section: Introductionmentioning
confidence: 99%